Effect of Transformational Leadership on Job Satisfaction and Job Performance - Kifayat Ullah Mian; Dr. Iqbal Amin Khan (`, 2025)
This study investigated the perceptions of secondary schools teachers and heads regarding the effect of transformational leadership on job satisfaction and job performance and also found the relationship between transformational leadership and job satisfaction, transformational leadership and job performance and job satisfaction and job performance. The population of research was all the secondary schools heads and teachers of district Malakand. There were total 83 high and higher secondary school in district Malakand in which there were 819 teachers are working in these schools. Therefore the total population of the study will be comprised on 83 heads and 819 teachers. The researcher were used the area or cluster sampling technique selected 20 heads randomly for the collection of data in which 11 heads were male and 9 heads are female. The total numbers of male and female teacher were 200. Three questionnaires were developed after review of related literature and previous studies. The transformational leadership variable containing eleven statements, job satisfaction containing sixteen statements while other variable job performance containing 19 statements. The researcher used SPSS for data analysis. The tests applied for data analysis were independent sample t-test. The results show that the value of coefficient of correlation was found (0.276) at 0.01 level of significance, therefor there is positive significant weak relationship between transformational leadership and job satisfaction It shows that if the principal follows transformational leadership style then his job satisfaction level will be increased, The results show that the value of coefficient of correlation was found (0.358) at 0.01 level of significance, therefor there is positive significant moderate relationship between transformational leadership and job performance It shows that if the principal follows transformational leadership style then his job performance level will be increased, The results show that the value of coefficient of correlation was found (0.247) at 0.05 level of significance, therefore, there is positive non-significant weak relationship between job satisfaction and job performance It shows that if the Job satisfaction level increase then his job performance level will be increased. No significant difference was found between the perception of heads and teachers of secondary schools regarding transformational leadership style, Job satisfaction and job performance. It is recommended that arrangement of pre-service, in- service training and refresher courses for heads may be a worthwhile strategy for improving the leadership abilities of secondary school principals. Keywords: transformational leadership, job satisfaction, Job performance, School sector.